Chiral covalent triazine framework CC-DMP CCTF@SiO2 core–shell microspheres used for HPLC enantioseparation. (28th February 2023) - Zhu, Yu-Lan; Guo, Ping; Yang, Yu-Ping; Ran, Xiao-Yan; Liu, Cheng; Wang, Bang-Jin; Zhang, Jun-Hui; Xie, Sheng-Ming; Yuan, Li-Ming
Abstract : CC-DMP CCTF@SiO2 core–shell composite microspheres for chiral separation. Abstract : Chiral covalent triazine frameworks (CCTFs), as emerging chiral organic porous polymer materials, have many special properties, such as being rich in nitrogen, having a large surface area, adjustable porosity, and high chemical stability, etc., making them an attractive separation medium for HPLC enantioseparation. Herein, a novel chiral core–shell composite CC-DMP CCTF@SiO2 with uniform spherical particles was synthesized by an in situ growth method. The prepared chiral core–shell microspheres CC-DMP CCTF@SiO2 were adopted to resolve chiral compounds by HPLC. The results showed that the CC-DMP CCTF@SiO2 packed column exhibited good separation performance and high column efficiency ( e.g., 17 580 plates m −1 for 4-methylbenzhydrol) under a low column back pressure (5–9 bar) for HPLC separation of different chiral compounds such as alcohols, amines, ketones, and so on. Among them, the resolution values of naringenin and 1-phenyl-1, 2-ethanediol were 4.24 and 4.09, respectively. Comparing the chiral recognition capacity of the CC-DMP CCTF@SiO2 packed column with those of commercial Chiralpak AD-H and the previously reported CCOFs@SiO2 (CTpBD@SiO2, β-CD-COF@SiO2 ) columns, the CC-DMP CCTF@SiO2 packed column can be complementary to the Chiralpak AD-H and CCOFs@SiO2 columns. The effects of the injection amount and column temperature on the separation process were also studied. The CC-DMP CCTF@SiO2 packed column exhibited good reproducibility and stability after multiple injections. The relative standard deviations (RSDS ) of the retention time and peak area for repeated separation of 4-methylbenzhydrol ( n = 5) were 0.45% and 0.87%, respectively. This work suggests that the chiral CC-DMP CCTF@SiO2 core–shell microsphere composite has a promising application as a novel CSP material in HPLC.